The existence and uniqueness of positive monotone solutions for a class of nonlinear Schrödinger equations on infinite domains - Sun, Y.; Liu, Lishan; Wu, Yong Hong (Elsevier, 2017)
© 2017In this paper, by constructing a new weighted norm method and analysis technique, we establish the conditions for the existence and uniqueness of positive monotone solutions to a class of nonlinear Schrödinger equations in planar exterior domains. Some examples are also given to demonstrate the application of our main results.